The democracy advantage : how democracies promote prosperity and peace - Halperin, Morton H. 1938- (A Council on foreign relations book, 2010)
"The Democracy Advantage provides an empirically-grounded analysis of the consistently positive development track record of poor countries with democratic governments versus those with more oppressive political systems. Building on the democratic peace literature, Halperin, Siegle, and Weinstein connect the dots of how democracy and development contribute to lower levels of intrastate conflict and popular support for extremist ideologies. This analysis provides a foundation for a series of policy recommendations for how democracy can become a more central feature of US and international engagement in the developing world. The Democracy Advantage is an evenly argued liberal internationalist justification for making democracy a central feature of US foreign policy." -- Book cover